PENGARUH PENGGUNAAN TEKNIK PEMODELAN TERHADAP KETERAMPILAN MENULIS CERITA PENDEK - Fiona, Finda; Ratna, Ellya; Noveria, Ena (Universitas Negeri Padang, 2016)
ABSTRACTÂ This research aims to describe skills in writing short story of studentsclass X SMA Negeri 1Lubuk Sikaping before and after use modeling techniques, with describe the effect of the use of modeling techniques in writing short storyof studentsclass X SMA Negeri 1Lubuk Sikaping. The type of this research is quantitative research done using experimental design.The results of this research areshort story writing skills of students class X SMA Negeri 1Lubuk Sikaping before use modeling techniques is more fairly and grades LdC, and after use modeling techniques is good and grades B, and based on t-test, results concluded that the use of modeling techniques influence the short story writing skills class X SMA Negeri 1 Lubuk Sikaping because ttable<tcount (1,68<10,32).Â Kata kunci: pengaruh, teknik pemodelan, cerita pendek.